Analisis Kesalahan Penulisan Aksara Jawa Pada Papan Nama Jalan di Kota Surakarta - Nugroho, Himawan Adi; Sulaksono, Djoko; Rahmat, Rahmat (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2023)
This study aims to describe the unfitting usage of Aksara Jawa (Javanese script) found on the street name signs in Surakarta City. This study used descriptive qualitative method with case studies approach Surakarta City. Data sources used in this study include places (street name signs bards with Javanese script) and documents (Paugeran Sriwedari 1926 and tiga Gubernur 1996). Purposive sampling method is selected for this study for specific purpose. Findings indicate that (1) Unfitting usage of carakan, sandhangan, murda, and swara in Aksara Jawa was found on the street name signs in Surakarta City in accordance with Sriwedari and  Tiga Gubernur guideliness.